Insights from comparative hearing research - Manley, Geoffrey A.; Popper, Arthur N.; Fay, Richard R.; Koppl, Christine (Springer Handbook of Auditory Research, 2014)
The hearing organs of non-mammals, which show quite large and systematic differences to each other and to those of mammals, provide an invaluable basis for comparisons of structure and function. By taking advantage of the vast diversity of possible study organisms provided by the "library" that is biological diversity, it is possible to learn how complex functions are realized in the inner ear through the evolution of specific structural, cellular and molecular configurations. Insights from Comparative Hearing Research brings together some of the most exciting comparative research on hearing and shows how this work has profoundly impacted our understanding of hearing in all vertebrates.